Fantasy, Colonialism, and the Middle Landscape. - ATTEBERY, BRIAN (Mythlore)
Weaving together Anglo-American folklore, the Indian captivity narrative genre, and science fiction and fantasy with Midwest settings, Attebery explores the lasting influence of the pastoral chronotope of the "middle landscape" and its entanglement with colonialism and empire. Scholar Guest of Honor Address, Mythcon 53.